POTENSI TUMBUHAN LOKAL SEBAGAI SUMBER BELAJAR BIOLOGI - Kistantia Elok Mumpuni; Herawati Susilo; Fatchur Rohman (Universitas Sebelas Maret, 2014)
This research aimed to ascertain: 1) inventoring and documenting local plantsin surrounding Muria mountain as an effort to do conservation of local potential in Kudus; 2) utilizing local plants as a source of learning biology. Research started with descriptive exploratory aboutlocal plants surrounding Muria mountain. After it, analyze the potential of local plants as a source of learning. The result from explorative descriptive shows that local plants parijoto, pisang byar, jeruk pamelo, pomegranate, pakis kathok and pakis have great potential to be developed. local plants can potentially be as learning resource for learning biology for high school students based on the study of literature. Keywords: local potential, local plants, learning resources